The Effect of Pricing Strategy, Promotion, and Online Reviews on Consumer Purchasing Decisions: An Empirical Study - Anik Sofiatun Amanah; Zainal Zawir Simon (Research of Economics and Business, 2026)
The rapid growth of digital commerce has intensified competition among online sellers, requiring businesses to understand the factors that influence consumer purchasing decisions in digital marketplaces. However, empirical evidence on how price, promotion, and electronic word of mouth particularly online customer reviews and ratings shape purchasing decisions in the TikTok Shop ecosystem remains limited. Therefore, this study aims to examine the effects of price, promotion, online customer reviews, and online customer ratings on purchasing decisions, and to review these relationships from an Islamic perspective. This study uses an explanatory research design with a population consisting of TikTok Shop consumers in North Jakarta and a sample of 125 respondents. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that price, promotion, and online customer reviews have a positive and significant effect on purchasing decisions, whereas online customer ratings do not. These findings provide empirical evidence on consumer behavior in the TikTok Shop marketplace and highlight the importance of pricing strategies, promotional activities, and credible online reviews in influencing purchasing decisions in digital commerce environments.